Synthesis, Characterization and Antibacterial Activity of Metal Complexes of N-(1-morpholinobenzyl)acetamide - RAMAN, N.; RAVICHANDRAN, S. (Asian Journal of Chemistry, 2010)
Solid complexes of a new Mannich base, N-(1-morphoIinobenzyl) acetamide (MBA) with Cu(ll), Ni(I1) Co(ll), and Zn(II) complexes have been synthesised and characterised by spectral studies, molar conductance, magnetic susceptibility and elemental analyses. The antibacterial activity of the complexes has also been studied.